ANALISIS CITRAAN DALAM NOVEL AKU TAK MEMBENCI HUJAN KARYA SRI PUJI HARTINI - Rauzatul Funna; Syahriandi; Maulidawati (Global Action and Education for Society, 2026)
This study aims to describe the imagery in the novel Aku Tak Membenci Hujan Karya Sri Puji Hartini. The method used is descriptive qualitatifeith a content analysis approach. The data analyzaed focused on sevaen images, namely visual imagery, auditory imagery, motion imagery, tactile imagery, olfactory imagery, gustatory imagery, and mental/feeling imagery. The results of the study show that in the novel Aku Tak Membenci Hujan Karya Sri Puji Hartini there are 127 images. The imagery is in the from of visual imagery with a total of 61 data, auditory imagery with a total of 20 data, motion imagery with a total of 14 data, tactile imagery with a total of 23 data, gustatory imagery with a total of 2 data, mental/feeling imagery with a total of 10 data. With tihis study, it is hopped that readers can utiliza the good results to deepen their ability to understand the essence of imagery in a literary work, especially novels.